2005
DOI: 10.1002/prot.20651
|View full text |Cite
|
Sign up to set email alerts
|

Focused library design in GPCR projects on the example of 5‐HT2c agonists: Comparison of structure‐based virtual screening with ligand‐based search methods

Abstract: The aim of this study was to investigate the usefulness of structure-based virtual screening (VS) for focused library design in G protein-coupled receptors (GPCR) projects on the example of 5-HT(2c) agonists. We compared the performance of structure-based VS against two different homology models using FRED for docking and ScreenScore, FlexX, and PMF for rescoring with the results of 12 ligand-based similarity searches using four different query compounds and three different similarity metrics (Daylight, FTree,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…In 2003, Cavasotto and coworkers demonstrated the applicability of this scoring function to the identification of the binding site of retinal in bovine rhodopsin and to the discrimination between binders and nonbinders of rhodopsin [67]. Similarly, using molecular databases spiked with known binders, a number of studies based on combinations of different scoring functions (such as Gold [68], Dock [69], CScore (Tripos), Fresno [70], Score [71], FlexX [72], and PMF [66]) have demonstrated the applicability of molecular docking at GPCR models to virtual screening [9,10,73]. In agreement with the expectations set by these studies, a variety of docking programs and scoring functions have been successfully applied to the discovery of novel ligands for a plethora of GPCRs, including neurorokinin [74,75], adrenergic [76], chemokine [75,77], dopamine [75], serotonin [75,78], cannabinoid [79], and free fatty acid receptors [80], among others.…”
Section: Structure-based Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Cavasotto and coworkers demonstrated the applicability of this scoring function to the identification of the binding site of retinal in bovine rhodopsin and to the discrimination between binders and nonbinders of rhodopsin [67]. Similarly, using molecular databases spiked with known binders, a number of studies based on combinations of different scoring functions (such as Gold [68], Dock [69], CScore (Tripos), Fresno [70], Score [71], FlexX [72], and PMF [66]) have demonstrated the applicability of molecular docking at GPCR models to virtual screening [9,10,73]. In agreement with the expectations set by these studies, a variety of docking programs and scoring functions have been successfully applied to the discovery of novel ligands for a plethora of GPCRs, including neurorokinin [74,75], adrenergic [76], chemokine [75,77], dopamine [75], serotonin [75,78], cannabinoid [79], and free fatty acid receptors [80], among others.…”
Section: Structure-based Methodologiesmentioning
confidence: 99%
“…Thus, structure-function studies of GPCRs relied heavily on sequence and phylogenetic analyses, rhodopsin-based homology modeling, and docking studies supported by site-directed mutagenesis and ligand structure-activity relationships (SAR) data [5,6]. In this context, experimentally validated GPCR homology models have proven to be valuable tools for lead identification, and the scientific literature flourished with successful rational drug design and virtual screening examples [7][8][9][10][11]. In 2007 Kobilka and coworkers unveiled the 3D crystal structure of the human β 2 -adrenergic receptor (β 2 -AR), finally providing the long awaited proof that the structure of GPCRs generally resembles that of rhodopsin [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To address this, a number of groups have sought to develop docking-based QSAR models [98,109,[117][118][119][120][121][122][123][124]. A combination of ligand-supported homology modeling and 3D-QSAR models has been applied to the discovery of A2a adenosine receptor antagonists, for example [124].…”
Section: Lead Optimization-sar Interpretation Potency Selectivity mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] Among these studies, it has been demonstrated that the homology models of dopamine D3, muscarinic M1, vasopressin V1a receptors, and 5HT 2c were reliable enough to retrieve known antagonists via structurebased virtual screening from several compound databases. 7,14 Rhodopsin-based homology models of the R 1A receptor could be used as the structural basis for the lead finding and optimization through the application of a hierarchical virtual screening procedure. 6 In addition, virtual screening has been successfully performed to identify a submicromolar antagonist of the neurokinin-1 receptor based on a ligand-supported homology model.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] However, the relatively low global sequence identity between the structure-unknown GPCRs and bovine rhodopsin is generally considered to be insufficient for reliable homology modeling. 6 The different conformation states of GPCRs could also be induced by various types of bound ligand.…”
mentioning
confidence: 99%